Julie of the wolves - George, Jean Craighead 1919- (HarperCollins Publishers, 1972)
While running away from home and an unwanted marriage, a thirteen-year-old Eskimo girl becomes lost on the North Slope of Alaska and is befriended by a wolf pack.